Dual‐function fluorescent probe for cancer imaging and therapy. (20th September 2015) - Cui, Hongjing; Wang, Ran; Zhou, Ying; Shu, Chang; Song, Fengjuan; Zhong, Wenying
Abstract: To date, several fluorescent probes modified by a single targeting agent have been explored. However, studies on the preparation of dual‐function quantum dot (QD) fluorescent probes with dual‐targeting action and a therapeutic effect are rare. Here, a dual‐targeting CdTe/CdS QD fluorescent probe with a bovine serum albumin–glycyrrhetinic acid conjugate and arginine‐glycine‐aspartic acid was successfully prepared that could induce the apoptosis of liver cancer cells and showed enhanced targeting in in vitro cell imaging. Therefore, the as‐prepared fluorescent probe in this work is an efficient diagnostic tool for the simultaneous detection of liver cancer and breast cancer cells. Copyright © 2015 John Wiley & Sons, Ltd.